2012
DOI: 10.2174/092986712801323171
|View full text |Cite
|
Sign up to set email alerts
|

Trigonelline: A Plant Alkaloid with Therapeutic Potential for Diabetes and Central Nervous System Disease

Abstract: There is evidence that Trigonella foenum-graecum L. (fenugreek), a traditional Chinese herb, and its components are beneficial in the prevention and treatment of diabetes and central nervous system disease. The pharmacological activities of trigonelline, a major alkaloid component of fenugreek, have been more thoroughly evaluated than fenugreek's other components, especially with regard to diabetes and central nervous system disease. Trigonelline has hypoglycemic, hypolipidemic, neuroprotective, antimigraine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
173
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(181 citation statements)
references
References 53 publications
(88 reference statements)
6
173
0
2
Order By: Relevance
“…MNA displayed a profile of antithrombotic activity in vivo (Chlopicki et al, 2007). Trigonelline (down-regulated) is a plant hormone (Evans and Tramontano, 1981) which has been reported as having therapeutic potential in the prevention and treatment of diabetes and central nervous system disease (Zhou et al, 2012). Quinolinate (down-regulated) studies (Guillemin, 2012) showed that quinolinic acid has toxic effects, e.g., inducing mood depression.…”
Section: H Nmr Analysismentioning
confidence: 99%
“…MNA displayed a profile of antithrombotic activity in vivo (Chlopicki et al, 2007). Trigonelline (down-regulated) is a plant hormone (Evans and Tramontano, 1981) which has been reported as having therapeutic potential in the prevention and treatment of diabetes and central nervous system disease (Zhou et al, 2012). Quinolinate (down-regulated) studies (Guillemin, 2012) showed that quinolinic acid has toxic effects, e.g., inducing mood depression.…”
Section: H Nmr Analysismentioning
confidence: 99%
“…In Nigeria, it is locally known as Tonaposo in Yoruba language (Elufioye et al, 2012) while in Pakistan, it is called Gul-abbas (Dhar et al, 1968). Phytochemical investigation reveals the presence of β-sitosterol, ursolic acid, amino acids, β-stigmasterol (Singh and Mittal, 2012), phytol (Siddiqui et al, 1994) in the aerial parts while rotenoids (Xu et al, 2010) and trigonelline (Zhou et al, 2012) alkaloid have been characterized from the roots. The plant is known to possess medicinal properties across different cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of the aerial parts are also used as purgative and in the treatment of dysentery (Encarnacion et al, 1998) and diarrhea (Holdsworth, 1992;Comerford, 1996). In Chinese traditional medicine, the root of this plant is used as an anti-diabetic (Zhou et al, 2012). Several literature reports on scientific studies on various parts of the plant suggest the presence of clinically important pharmacologic properties (as claimed), including antibacterial (Eneji et al, 2011), anti-viral (Wong et al, 1992, anti-inflammatory (Nath et al, 2010) and treatment for dysentery (Shaik et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Há evid ias de ue o fe o-g ego e seus componentes são benéficos na prevenção e tratamento da diabetes e de doenças do sistema nervoso central. 19 O principal alcaloide desta espécie é a trigonelina, sobre a qual, também foi reportada diversas atividades, como hipoglicêmica, hipolipidêmica, neuroprotetora, antienxaqueca, sedativa, antibacteriana, A N-etil-L-prolina (1), trigonelina (2) e betaína (3) são consideradas de importância ecológica. A sua acumulação em plantas faz parte de um mecanismo de adaptação em resposta ao estresse osmótico (osmoprotetores), incluindo estresse por déficit de água e por níveis altos de salinidade.…”
unclassified